24.8k views
4 votes
Whats the answer to 29-(2c+3)=2(c+3)+c

User Jeremias
by
5.5k points

2 Answers

3 votes

Answer:

Solution for 29-(2c+3)=2(c+3)+c equation:

Simplifying

29 + -1(2c + 3) = 2(c + 3) + c

Reorder the terms:

29 + -1(3 + 2c) = 2(c + 3) + c

29 + (3 * -1 + 2c * -1) = 2(c + 3) + c

29 + (-3 + -2c) = 2(c + 3) + c

Combine like terms: 29 + -3 = 26

26 + -2c = 2(c + 3) + c

Reorder the terms:

26 + -2c = 2(3 + c) + c

26 + -2c = (3 * 2 + c * 2) + c

26 + -2c = (6 + 2c) + c

Combine like terms: 2c + c = 3c

26 + -2c = 6 + 3c

Solving

26 + -2c = 6 + 3c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-3c' to each side of the equation.

26 + -2c + -3c = 6 + 3c + -3c

Combine like terms: -2c + -3c = -5c

26 + -5c = 6 + 3c + -3c

Combine like terms: 3c + -3c = 0

26 + -5c = 6 + 0

26 + -5c = 6

Add '-26' to each side of the equation.

26 + -26 + -5c = 6 + -26

Combine like terms: 26 + -26 = 0

0 + -5c = 6 + -26

-5c = 6 + -26

Combine like terms: 6 + -26 = -20

-5c = -20

Divide each side by '-5'.

c = 4

Simplifying

c = 4

User Datguywhowanders
by
5.6k points
5 votes

Answer:

29-(2c+3)=2(c+3)+c=

We move all terms to the left:

29-(2c+3)-(2(c+3)+c)=0

We get rid of parentheses

-2c-(2(c+3)+c)-3+29=0

Explanation:

User Biegleux
by
4.9k points